2012
DOI: 10.1080/02699931.2011.638906
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias to violent images in survivors of dating violence

Abstract: This study investigated the time-course characteristics of attentional bias, such as vigilance and maintenance, towards violent stimuli in dating violence (DV) survivors. DV survivors with PTSD symptoms (DV-PTSD group; n=14), DV survivors without PTSD symptoms (Trauma Control group; n=14), and individuals who were never exposed to dating violence (NDV group; n=15) viewed slides that presented four categories of images (violent, dysphoric, positive, and neutral) per slide, for ten seconds. Our results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 27 publications
5
44
1
Order By: Relevance
“…The hypothesized orienting bias toward disgusted and fearful expressions in the veteran PTSD group was not observed. This null finding is consistent with visual search studies as well as other eye tracking studies that have failed to observe facilitated detection of threat in PTSD. Pineles et al suggest that facilitated detection of threat may be weak or absent in PTSD because the disorder is characterized by ruminations and intrusions related to a past event.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The hypothesized orienting bias toward disgusted and fearful expressions in the veteran PTSD group was not observed. This null finding is consistent with visual search studies as well as other eye tracking studies that have failed to observe facilitated detection of threat in PTSD. Pineles et al suggest that facilitated detection of threat may be weak or absent in PTSD because the disorder is characterized by ruminations and intrusions related to a past event.…”
Section: Discussionsupporting
confidence: 92%
“…Fearful and disgusted expressions did hold attention longer in veterans with PTSD compared to happy expressions, a gaze pattern that distinguished veterans with PTSD from both veterans without PTSD and nonveteran controls. This bias was sustained over the 3 s trials, consistent with other eye tracking studies that have observed a prolonged maintenance bias on negatively valenced stimuli in PTSD . This finding is also in line with the observation that individuals with PTSD dwell longer on trauma‐related distractors in visual search tasks, although the present findings, as well as the eye tracking findings of Kimble et al, suggest that the maintenance bias in combat‐related PTSD is not circumscribed to trauma‐specific content, but instead targets threatening stimuli more broadly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, other studies [55, 60•] have found attentional bias toward general threat images to be correlated with greater severity of posttraumatic stress symptoms. With particular relevance to this problem, studies that used eye tracking [61], a measure of attentional bias that does not require verbal or non-ocular motor responses, showed increased number of initial fixations to trauma-related words in PTSD compared to trauma exposed non-PTSD subjects, suggesting attentional bias toward aversive cues is likely to be PTSD specific rather than a result of trauma per se [62•, 63]. Overall, it appears that attention bias abnormalities related to PTSD-prediction depend in part on the specific task and the studies’ environment (i.e., laboratory versus naturalistic set-up.…”
Section: Behavioral Markers (N=7)mentioning
confidence: 99%